Normal values of antistreptolysin O for adults ages 30 to 70 in Syria: A cross sectional study. (November 2021) - Brimo Alsaman, Muhamad Zakaria; Shashaa, Mohammad Nour; Alkarrash, Mohamad Shadi; Kitaz, Mohammad Nour; Zazo, Aya; Alhamid, Ahmad; Zazo, Rama; Haj Kadour, Samer
Abstract: Background: Group A Streptococcus is a very common pathogen which infects a large scale of people around the world causing many symptoms such as scarlet fever, sinusitis, and pneumonia. Most strains of group A and many other strains of group C and G Streptococcus bacteria secreted antigen called Streptolysin O. Anti-streptolysin O (ASO) is an antibody produced against streptolysin O that rises after 1 week of infection by streptococcus bacteria, which helps in diagnosing this type of infectious diseases. We conducted a Cross-Sectional study to determine the Upper Limit of Normal (ULN) for healthy adult in Aleppo, Syria. Materials and methods: A sero-epidemiological cross-sectional study was conducted from September to October in 2019. ASO titers were determined on 267 healthy patients' companions who visited Aleppo University Hospital. Geometric mean titer and Upper Limit of Normal of ASO were calculated according to sex, age and residency. Upper Limit of Normal were defined as the 80th percentile. Results: Out of 267 participants; 126 (45.7%) were males and 150 (54.3) were females. The Upper Limit of Normal for total participants was 210.8 IU/ml. There was no significant difference (P-value > 0.05) among males (204.6 IU/ml) and females (225.8 IU/ml). In contrast to sex, there was a significant difference (P-value < 0.05) according to age groups, where the highest Upper Limit of Normal was in the 30–39 age group (256.0 IU/ml). Conclusion: ASO test is a common, easy, cheap method, so getting enough data about it is very important in the developing countries (such as Syria). In Aleppo, Syria we found that the ULN was higher than ULN from other studies. There was no significant difference according to sex and residency. On the other hand, there was significant difference according to age groups. Highlights: The Upper Limit of Normal for total participants was 210.8 IU/ml. We found that the ULN was higher than ULN from other studies. There was significant difference in ULN according to age groups.